Influence of included angle and sill slope on air entrainment of triangular planform labyrinth weirs - Emiroglu, ME; Baylar, A (Asce-Amer Soc Civil Engineers, 2005)
Aeration of water downstream of weirs is caused by air being carried by the overfalling jet into the downstream receiving pool. The air entrainment characteristics of straight weirs have been measured and analyzed by a number of investigators. However, labyrinth weirs, where the weir sill is not straight in planform, thus increasing their length, have received little attention in this respect. This paper investigates the effect of varying the weir-included angle and the weir sill slope on the air entrainment rate of a triangular labyrinth weir. It is demonstrated that the air entrainment rate of a triangular labyrinth weir is better than that of an equivalent straight weir and that this advantage becomes more pronounced as the weir sill slope increases. Regression equations were obtained for triangular labyrinth weirs relating the air entrainment rate to drop height, weir discharge, weir-included angle, and weir sill slope.
Keywords: aeration; air entrainment; hydraulic jets; weirs; slopes